THE EFFECT OF AEROBIC AND ANAEROBIC EXERCISES ON SERUM TRIMETHYLAMINE N-OXIDE (TMAO) LEVELS IN FRUCTOSE-MEDIATED RAT METABOLIC SYNDROME MODEL - Karaman, Muhammed Emre; Arslan, Cengiz; Gürsu, Mehmet Ferit; Kaymaz, Tuğçe (Ataturk Universitesi, 2021)
In this study, it was aimed to investigate the change in serum levels of trimethylamine N-oxide (TMAO), which is thought to trigger cardiovascular diseases with its changes in the circulatory system, with aerobic and anaerobic exercise applications in the high fructose-mediated rat metabolic syndrome model. A total of 24 male Wistar-Albino rats were used in the study. The rats were housed in study rooms with controlled humidity, temperature and lighting throughout the study. Rats were divided into 4 groups as Control group, Metabolic Syndrome Group, Metabolic Syndrome + Aerobic Exercise Group and Metabolic Syndrome + Anaerobic Exercise group. Drinking water containing 30% fructose was used to induce the metabolic syndrome. Metabolic syndrome induction was confirmed by checking serum glucose, triglyceride and high density lipoprotein (HDL) levels at the 8th week of the study. At the end of the study, the rats were decapitated and TMAO levels were measured in serum samples by ELISA method. The TMAO levels of rats with metabolic syndrome and without exercise were statistically significantly higher than the control group (p<0.001). Although both exercise inventions decreased TMAO levels, which increased with metabolic syndrome, the decrease after anaerobic exercise application was statistically significant (p<0.05). It was observed that different exercise inventions affected serum TMAO levels in rats with metabolic syndrome. According to this result, the dysbiosis of the microflora and the resulting TMAO in rats with metabolic syndrome can be improved by the metabolic and hormonal effects of exercise. This is the first study to show that anaerobic exercise can reduce circulating levels of TMAO and can be an effective method in the treatment of diseases such as metabolic syndrome and cardiac syndrome. © 2021, Ataturk Universitesi. All rights reserved.
FRUKTOZ ARACILIKLI SIÇAN METABOLİK SENDROM MODELİNDE AEROBİK VE ANAEROBİK EGZERSİZLERİN SERUM TRİMETİLAMİN N-OKSİT (TMAO) DÜZEYLERİNE ETKİSİ
Keywords: aerobic exercise; anaerobic exercise; metabolic syndrome; trimethylamine N-oxide